EVALUASI KUALITAS WEBSITE SEKOLAH SMA NEGERI 6 JAKARTA DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) BERDASARKAN PERSPEKTIF WARGA SEKOLAH - Khodadat Azizy Jeser (2023)
Website is a means to disseminate information by utilizing technology in the form of internet networks. Currently, most of the schools already have website facilities that are used as a means of distributing information such as announcements, school agendas, and other important information. To measure how good the quality of the school's website is, evaluation can be done in the form of a website quality test using the WebQual 4.0 method which is packaged in the form of a questionnaire, where there are three dimensions in it, namely usability quality, information quality, and service interaction quality which are then tested through calculation techniques namely Importance Performance Analysis. The research was conducted on school citizens with a total of 346 respondents divided into several sample groups (Proportional Stratified Random Sampling). The hypothesis tested using the Paired T-test method to prove the truth of the hypothesis based on the results of research on the questionnaire and the congruence level test to find out how high the level of congruence is on all indicators of the actual dimension and the expected dimension. The results of the Paired T-test show that the hypothesis is not accepted with a significance of 0.000 with the value of Tcount < Ttable, also the level of congruence is not yet close to its peak (92.17%). The results of the quadrant analysis and GAP analysis show that all indicators in each quadrant have negative GAP values with an average GAP of -0.3355, so that all indicators still have not good actual performance. Recommendations based on the results of an analysis that is realized directly by the school's IT team by rebuilding the school's website.